Mèmes, gifs et communication cognitivo-affective sur Internet - Albin Wagener (Communication)
The author introduces an approach that may give us a better grasp of the communicational role of memes and gifs, measure their impact on research in the digital humanities, and define them as media signs in online interactional communications. It’s a deliberately theoretical and conceptual approach originating in the pragmatic observation of digital social relations and the creative processes associated with them and is based on examples of memes and gifs currently in circulation on social media and platforms such as Facebook, Twitter, and WhatsApp.